1973
DOI: 10.1159/000208349
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Bone Marrow Transplantation in Experimental <sup>32</sup>P-Induced Aplastic Anemia after Conditioning with Antilymphocyte Serum

Abstract: Aplastic anemia was produced with 32P in rabbits with and without splenectomy. Transient hemopoietic engraftment without graft versus host (GvH) was seen after conditioning with antilymphocyte serum (ALS) and infusion of allogeneic marrow from a strain that is known to cause fatal secondary disease if total body irradiation is used for conditioning. More takes could be achieved in the splenectomized group but in both groups the takes were only transient. The absence of GvH was shown to be probably d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1973
1973
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…A similar beneficial and often more prolonged effect was obtained by the use of allogeneic anti-donor or anti-recipient anti-lymphocyte ser um [17]. The results in our patients follow the rat model [16,17] more closely than the rabbit [8,9]. Despite extensive studies, no definite evi dence of chimaerism could be demonstrated in our patients.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…A similar beneficial and often more prolonged effect was obtained by the use of allogeneic anti-donor or anti-recipient anti-lymphocyte ser um [17]. The results in our patients follow the rat model [16,17] more closely than the rabbit [8,9]. Despite extensive studies, no definite evi dence of chimaerism could be demonstrated in our patients.…”
Section: Discussionsupporting
confidence: 79%
“…All were polytransfused with random blood products. In the rabbit with benzene-and 32P-induced AA and in several clinical patients, split and transient haemopoietic engraftments have been achieved after conditioning with ALG followed by mar row infusion [8][9][10][11][12], Despite of histocompatibility differences between donor and recipient, GvH has not been observed. Split chimaerism in the rabbit was of a rather constant pattern; donor erythrocytes, granulocytes and B lymphocytes took while T lymphocytes remained of host type [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Speck and Kissling [4, 5]in Basel used experimental rabbit models of benzene- and 32 P-induced marrow aplasia in rabbits, and demonstrated that ALG and mismatched bone marrow could rescue them from aplasia. Subsequent clinical trials in humans showed that the marrow infusion was unnecessary for autologous haematological recovery after ATG therapy [6].…”
Section: Introduction: Development Of Antithymocyte Globulin For the mentioning
confidence: 99%